The role of executive function in children's source monitoring with varying retrieval strategies - Earhart, Becky; Roberts, Kim P. (Frontiers in Psychology, 2014)
Previous research on the relationship between executive function and source monitoring in young children has been inconclusive, with studies finding conflicting results about whether working memory and inhibitory control are related to source-monitoring ability. In this study, the role of working memory and inhibitory control in recognition memory after exposure to multiple sources, and in source monitoring with two different retrieval strategies were examined. Children (N = 263) aged 4 to 8 participated in science activities with two sources. They were later given a recognition and source-monitoring test, and completed measures of working memory and inhibitory control. During the source-monitoring test, half of the participants were asked about sources serially (one after the other) whereas the other half of the children were asked about sources in parallel (considering both sources simultaneously). Results demonstrated that working memory was a predictor of source-monitoring accuracy in both conditions, but inhibitory control was only related to source accuracy in the parallel condition. When age was controlled, these relationships were no longer significant, suggesting that a more general cognitive development factor is a stronger predictor of source monitoring than executive function alone. Interestingly, the children aged 4 to 6 years made more accurate source decisions in the parallel condition compared to those in the serial condition. The older children (aged 7 to 8) were more accurate than the younger children, and their accuracy did not differ as a function of interview condition. Suggestions are provided to guide further research in this area that will clarify the diverse results of previous studies showing executive function is a cognitive prerequisite for effective source monitoring.